FATIGUE LIFE ANALYSIS OF FILLET WELDS OF TRANSFORMER OIL TANK WITH WELDING DEFECTS (MT) - CHEN Ben; JI YuChen; LIANG YiHeng; WANG XiaoSun (Jixie qiangdu)
The tank body of the transformer is filled with welds. Under vibration conditions, the fatigue damage of the tank often occurs at the internal defect position of the fillet weld. In order to analyze the effect of fillet weld defects on the fatigue life of the transformer tank, a finite element model of the transformer tank is established. According to the tank vibration test data, the fatigue analysis of the fillet welds on the sidewall of the tank was carried out in the nCode software, and the fatigue life of the fillet weld on the side wall of the lower transformer tank and the defect-free condition was obtained. Take the most dangerous fillet weld of the full tank sidewall fillet weld, and further establish a fillet weld model with partial defects, and analyze the influence law of the fatigue life of the fillet weld of the transformer tank when there are pores and slag defects. It was finally found that for slag inclusion defects, the greater the difference between the slag elastic modulus and the weld elastic modulus, the more likely it is to cause fatigue damage, and soft slag inclusions are more dangerous than hard slag inclusions; the increase in the size of pore defects will cause fatigue life reduce, the closer the pores is to the welding root, the shorter the fatigue life will be; and the pore defects are more likely to cause fatigue damage than the slag inclusion defects.